Salvage Fractionated Stereotactic Radiotherapy with or without Chemotherapy and Immunotherapy for Recurrent Glioblastoma Multiforme: A Single Institution Experience - Hasan, Shaakir; Chen, Eda; Lanciano, Rachelle; Yang, Jun; Hanlon, Alex; Lamond, John; Arrigo, Stephen; Ding, William; Mikhail, Michael; Ghaneie, Arezoo; Brady, Luther (Frontiers in Oncology, 2015)
Background: The current standard of care for salvage treatment of Glioblastoma Multiforme (GBM) is gross total resection and adjuvant chemoradiation for operable patients. Limited evidence exists to suggest that any particular treatment modality improves survival for recurrent GBM, especially if inoperable. We report our experience with fractionated stereotactic radiotherapy (fSRT) with and without chemo/immunotherapy, identifying prognostic factors associated with prolonged survival. Methods: From 2007 to 2014, 19 patients between 29 and 78 years old (median 55) with recurrent GBM following resection and chemoradiation for their initial tumor, received 18 – 35 Gy (median 25) in 3 – 5 fractions via Cyberknife fSRT. Clinical target volume (CTV) ranged from 0.9 to 152 cc. Sixteen patients received adjuvant systemic therapy with bevacizumab (BEV), temozolomide (TMZ), anti-epidermal growth factor receptor (125)I-mAb 425, or some combination thereof. Results: The median overall survival (OS) from date of recurrence was 8 months (2.5 – 61) and 5.3 months (0.6 – 58) from the end of fSRT. The OS at 6 and 12 months was 47% and 32%, respectively. Three of 19 patients were alive at the time of this review at 20, 49 and 58 months from completion of fSRT. Hazard ratios for survival indicated that patients with a frontal lobe tumor, adjuvant treatment with either BEV or TMZ, time to first recurrence >16 months, CTV < 36 cc, Recursive Partitioning Analysis (RPA) < 5, and ECOG (Eastern Cooperative Oncology Group) performance status < 2 were all associated with improved survival (P <0.05). There was no evidence of radionecrosis for any patient. Conclusions: Radiation Therapy Oncology Group (RTOG) 1205 will establish the role of reirradiation for recurrent GBM, however our study suggests that cyberknife with chemotherapy can be safely delivered, and is most effective in patients with smaller frontal lobe tumors, good performance status or long interval from diagnosis.